Microglia-mediated inflammatory destruction of neuro-cardiovascular dysfunction after stroke - Deng, Jiahong; Chen, Chenghan; Xue, Shuaishuai; Su, Daoqing; Poon, Wai Sang; Hou, Honghao; Wang, Jun (Frontiers in Cellular Neuroscience, 2023)
Stroke, a serious systemic inflammatory disease, features neurological deficits and cardiovascular dysfunction. Neuroinflammation is characterized by activation of microglia after stroke, which disrupts cardiovascular related neural-network and blood-brain barrier. Neural networks activate the autonomic nervous system to regulate the cardiac and blood vessels. Increased permeability of the blood-brain barrier and lymphatic pathways promotes the transfer of central immune components to peripheral immune organs and the recruitment of specific immune cells or cytokines, produced by the peripheral immune system, and thus modulates microglia in brain. In addition, spleen will also be stimulated by central inflammation to further mobilize the peripheral immune system. NK cells and Treg cells were generated to enter the central nervous system to suppress further inflammation while activated monocyte infiltrats the myocardium and cause cardiovascular dysfunction. In this review, we will focus on the microglia-mediated inflammation in neural networks, which results in cardiovascular dysfunction. Furthermore, we will discuss neuro-immune regulation in central-peripheral crosstalk and in which spleen is a vital part. Hopefully, this will benefit anchoring new therapeutic targets for neuro-cardiovascular dysfunction.